ANALISIS PROBLEMATIKA GURU DALAM MENGINTEGRASIKAN PEMBELAJARAN BIOLOGI DENGAN ISLAM DI MADRASAH ALIYAH NEGERI SE-KABUPATEN PESISIR SELATAN - Niken Mustika; Ardi Ardi (Al-Alam: Islamic Science Education Journal, 2025)
This study focuses on exploring the problems faced by biology teachers at Madrasah Aliyah Negeri Kabupaten Pesisir Selatan in integrating biology concepts with Islamic values. Using a descriptive qualitative approach, this study involved all biology teachers in the region through total sampling techniques. Data were collected through observation, semi-structured interviews, and documentation studies, then analyzed through data reduction, data presentation, and conclusion drawing. The results revealed that teachers faced various obstacles, such as a dichotomous view of science and religion, limited understanding of Islam, lack of professional training, and lack of adequate teaching materials and supporting facilities. These findings emphasize the importance of improving teacher competence, providing integrated teaching materials, and providing continuous institutional support so that the integration of Biology learning and Islamic values can be carried out more effectively. In addition, this study opens up opportunities for the development of more applicable and contextual learning models, thereby enriching the study of the integration of science and religion in Islamic education.